2006
DOI: 10.1136/bmj.39001.657755.be
|View full text |Cite
|
Sign up to set email alerts
|

Screening strategies for chronic kidney disease in the general population: follow-up of cross sectional health survey

Abstract: Objective To find an effective screening strategy for detecting patients with chronic kidney disease and to describe the natural course of the disease. Design Eight year follow-up of a cross sectional health survey (the HUNT II study). Setting Nord-Trøndelag County, Norway Participants 65 604 people (70.6 % of all adults aged ≥ 20 in the county). Main outcome measures Incident end stage renal disease (ESRD) and cardiovascular mortality monitored by individual linkage to central registries. Results 3069/65 604 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
178
3
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(202 citation statements)
references
References 34 publications
7
178
3
14
Order By: Relevance
“…Thus, a more beneficial and successful screening program would be one targeted at highrisk groups in which prevalence of the disease of interest is high, such as screening for CKD in patients with diabetes or hypertension. Recently, Hallan et al (10) nicely illustrated this issue in their 8-yr follow-up of a cross-sectional study (The Nord-Trøndelag Health Study [HUNT II Study]) in which they screened 65,604 adults in the general population of Norway. Defining CKD as an eGFR Ͻ60 ml/min per 1.73 m 2 , if the whole population were screened, then one would need to screen 20.6 individuals to identify one CKD case; whereas if screening were restricted to patients with diabetes, hypertension, or age Ͼ55 yr, then one would identify 93.2% of patients with CKD and would need only 8.7 individuals to identify one CKD case.…”
Section: Validity Of Screening Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a more beneficial and successful screening program would be one targeted at highrisk groups in which prevalence of the disease of interest is high, such as screening for CKD in patients with diabetes or hypertension. Recently, Hallan et al (10) nicely illustrated this issue in their 8-yr follow-up of a cross-sectional study (The Nord-Trøndelag Health Study [HUNT II Study]) in which they screened 65,604 adults in the general population of Norway. Defining CKD as an eGFR Ͻ60 ml/min per 1.73 m 2 , if the whole population were screened, then one would need to screen 20.6 individuals to identify one CKD case; whereas if screening were restricted to patients with diabetes, hypertension, or age Ͼ55 yr, then one would identify 93.2% of patients with CKD and would need only 8.7 individuals to identify one CKD case.…”
Section: Validity Of Screening Methodsmentioning
confidence: 99%
“…To date, few evidence-based effective screening strategies have been confirmed in the United States; however, Hallan et al (10) recently reported and compared different screening strategies for detecting patients with CKD in the general population of adults Ն20 yr of age in Nord-Trøndelag County, Norway. The authors used a cross-sectional health survey with 8 yr of follow-up (the HUNT II study).…”
Section: Previous Ckd Screening Effortsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of individuals who need to be screened to identify a single individual in whom a reasonably useful intervention could be offered is likely to be extremely large. Both the "false positive" and "false negative" rates would be dauntingly high using the current classification CKD schema (21).…”
Section: Egfr Should Not Be Used In Isolation As a Means For Screeninmentioning
confidence: 99%
“…1,2 Recently, chronic kidney disease (CKD) has been increasingly drawing attention as a high-risk factor for death from CVD, 3,4 and diabetic nephropathy is a major cause of CKD. 5 Moreover, an elevated albumin excretion rate, which is a useful marker of diabetic nephropathy, has been reported to be associated with increased risk of cardiovascular mortality. 6 The anklebrachial index (ABI) is a simple and useful method to assess peripheral artery disease (PAD).…”
Section: Introductionmentioning
confidence: 99%